Recurrent and current trends in the study of the Book of Psalms - N.L. deClaissé- Walford (Acta Theologica)
In the past one hundred years, two approaches to the study of the Book of Psalms have tended to dominate, namely form criticism and shape and shaping (canonical criticism). Other studies such as the theology of psalms, the poetics of psalms, the redaction of psalms, as well as psalms and intertextuality have also been done. These approaches to the Psalter will continue to be points of focus for studies – the recurrent trends. In the late 20th nd early 21st centuries, other approaches to the Psalter emerged such as, among others, rhetorical criticism, liberation theology, feminist criticism, the psalms and spirituality, and so forth – the current trends. This article offers a summary of the current state of the form critical and the shape and shaping studies of the Psalter – the recurrent trends – and then moves on to examine a number of the 21st-century approaches to the book of Psalms – the current trends. The article concludes with some tentative thoughts about the future of psalm studies in the 21st century.